The Regulation Effect of α7nAChRs and M1AChRs on Inflammation and Immunity in Sepsis - Song Hu; Yundong Wang; Hongbing Li (Hindawi Limited, 2021)
The inflammatory storm in the early stage and immunosuppression in the late stage are responsible for the high mortality rates and multiple organ dysfunction in sepsis. In recent years, studies have found that the body's cholinergic system can spontaneously and dynamically regulate inflammation and immunity in sepsis according to the needs of the body. Firstly, the vagus nerve senses and regulates local or systemic inflammation by means of the Cholinergic Anti-inflammatory Pathway (CAP) and activation of α7-nicotinic acetylcholine receptors (α7nAChRs); thus, α7nAChRs play important roles for the central nervous system (CNS) to modulate peripheral inflammation; secondly, the activation of muscarinic acetylcholine receptors 1 (M1AChRs) in the forebrain can affect the neurons of the Medullary Visceral Zone (MVZ), the core of CAP, to regulate systemic inflammation and immunity. Based on the critical role of these two cholinergic receptor systems in sepsis, it is necessary to collect and analyze the related findings in recent years to provide ideas for further research studies and clinical applications. By consulting the related literature, we draw some conclusions: MVZ is the primary center for the nervous system to regulate inflammation and immunity. It coordinates not only the sympathetic system and vagus system but also the autonomic nervous system and neuroendocrine system to regulate inflammation and immunity; α7nAChRs are widely expressed in immune cells, neurons, and muscle cells; the activation of α7nAChRs can suppress local and systemic inflammation; the expression of α7nAChRs represents the acute or chronic inflammatory state to a certain extent; M1AChRs are mainly expressed in the advanced centers of the brain and regulate systemic inflammation; neuroinflammation of the MVZ, hypothalamus, and forebrain induced by sepsis not only leads to their dysfunctions but also underlies the regulatory dysfunction on systemic inflammation and immunity. Correcting the neuroinflammation of these regulatory centers and adjusting the function of α7nAChRs and M1AChRs may be two key strategies for the treatment of sepsis in the future.